Study of the effectiveness of citrus pectin as a prebiotic - محمد ندى; ديمة الدياب; بلسم جريكوس (Latakia University Journal -Medical Sciences Series, 2024)
Plants and their products are a rich source of many compounds used in various pharmaceutical, food and pharmaceutical industries. Pectin, which is a structural polysaccharide in plants, is gaining increasing importance because of its multiple uses and benefits. However, in recent years, focus has been placed on the use of pectin as a prebiotic and its ability to modify intestinal microbial growth. This study aims to study the prebiotic effectiveness of pectin extracted from griffon and compare it with commercial pectin at two concentrations of 0.5% and 1%. The study found that pectin plays an important role as a prebiotic compared to a negative control that does not contain pectin, meaning that it enhances bacterial growth of the Lactobacillus species, and that an increase in the concentration of added pectin leads to an increase in bacterial growth.